2017
DOI: 10.2169/internalmedicine.56.7594
|View full text |Cite
|
Sign up to set email alerts
|

Non-uniform Progression of Chronic Tubulointerstitial Nephritis and Widespread Nephrocalcification in a Patient with Anorexia Nervosa

Abstract: Although patients with anorexia nervosa (anorexia) are known to show tubulointerstitial nephritis (TIN), the pathophysiology of its progression is not fully understood. We herein report a 31-year-old woman with anorexia who showed acute exacerbation of chronic kidney disease. Renal biopsy showed non-uniform chronic TIN; some areas were obsolete lesions and other areas were active lesions. In addition, many calcium-containing crystals were widely deposited in the distal tubules. The results suggest that chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…However, if prolonged, it causes irreversible changes, such as interstitial fibrosis, tubular atrophy, and medullary cyst formation [ 10 ]. Tubulointerstitial nephritis has also been reported as a complication of persistent hypokalemia in patients with anorexia nervosa [ 4 , 11 , 12 ]. The mechanism of tubulointerstitial nephritis in hypokalemia has not been established; however, the production of monocyte chemotactic protein 1 (MCP-1), a mediator of macrophage infiltration, is reportedly increased in the kidneys of rats with hypokalemia.…”
Section: Discussionmentioning
confidence: 99%
“…However, if prolonged, it causes irreversible changes, such as interstitial fibrosis, tubular atrophy, and medullary cyst formation [ 10 ]. Tubulointerstitial nephritis has also been reported as a complication of persistent hypokalemia in patients with anorexia nervosa [ 4 , 11 , 12 ]. The mechanism of tubulointerstitial nephritis in hypokalemia has not been established; however, the production of monocyte chemotactic protein 1 (MCP-1), a mediator of macrophage infiltration, is reportedly increased in the kidneys of rats with hypokalemia.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic hypokalemia is assumed to cause tubulo-interstitial damage by ammonia-mediated complement activation (so-called hypokalemic nephropathy) (13). Furthermore, Hasegawa et al reported a patient with AN associated with tubulo-interstitial nephritis and hypokalemia who had biopsy-proven widespread calcification of the renal tubules (14). Although the exact pathophysiology is unclear, several other reports have also described cases of nephrocalcinosis among patients with AN (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…While chronic hypokalemia leads to vacuolar lesions and tubulointerstitial nephritis (TIN), a recent case report describing renal biopsy of an eating disorder patient with intentional vomiting and hypokalemia showed non-uniform progression of TIN, suggesting additional factors contributing to renal disease, such as decreased renal perfusion [ 25 ]. Biopsy in this case revealed wide deposition of crystals and calcium deposits, suggesting nephrocalcinosis which can be seen in diuretic use [ 25 ].…”
Section: Pathophysiology Of Kidney Disease In Eating Disordersmentioning
confidence: 99%